2014
DOI: 10.1021/ol501643x
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Convenient Synthesis of 1,6-Di- or 1,2,5,6-Tetra-arylhexa-1,3,5-trienes by the Dimerization of Pd(0)-Complexed Alkenylcarbenes Generated from π-Allylpalladium Intermediates

Abstract: Pd(0)-complexed 3-aryl or 2,3-diaryl propenylcarbenes generated from α-silyl-, α-germyl-, or α-boryl-σ-allylpalladium intermediates undergo self-dimerization to provide 1,6-di- or 1,2,5,6-tetraarylhexa-1,3,5-trienes in good to high yields. This method allows the use of a π-allylpalladium intermediate for a carbenoid precursor. Furthermore, the obtained 1,2,5,6-tetraarylhexa-1,3,5-trienes exhibit aggregation-induced emission enhancement property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Notably, a substantial amount of 1,6‐diphenyl‐1,3,5‐hexatriene ( 4a ) was obtained in most cases. The formation of 4a is explained by the mechanism involving disproportionation of B , as shown in Scheme 7,15. In all cases, cyclopropanation occurred exclusively from the exo face of 2a , which was confirmed by NOE experiments.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Notably, a substantial amount of 1,6‐diphenyl‐1,3,5‐hexatriene ( 4a ) was obtained in most cases. The formation of 4a is explained by the mechanism involving disproportionation of B , as shown in Scheme 7,15. In all cases, cyclopropanation occurred exclusively from the exo face of 2a , which was confirmed by NOE experiments.…”
Section: Resultssupporting
confidence: 52%
“…In contrast, the formation of B might be incidental to the formation of A if CsF acts as a base, which would give 3a as a mixture of diastereomers. That is, inhibiting the generation of B would not only enhance the diastereoselection but also lead to an improvement in the yield of 3a because it is known that palladium carbenoids such as B are known to undergo dimerization 7,13c,15. We were please to find that the use of CsF in conjunction with 18‐crown‐6 improved the diastereoselection (Table 2, entries 2 and 6).…”
Section: Resultsmentioning
confidence: 96%
“…5,6 However, addition of MS 4A to prevent the formation of 4a by residual H 2 O failed (entry 6). 7 Although the catalyst loading could be reduced to 5 mol% without significant loss of catalytic activity, we were pleased to find that use of an excess amount of 2a (3 equiv to 1a) improved the yield of 3aa (entry 7). Besides the monodentate phosphine ligand, use of bidentate phosphine ligands also efficiently promoted the present reaction (entries 8−12).…”
Section: Resultsmentioning
confidence: 97%
“…3,4 Fillion and our recent studies on allylic gem-heterobimetallic species revealed individually that the distinct reactivities of allylic gem-palladium/metalloid species cannot be reached by hitherto reported allylpalladium species. [5][6][7][8] For example, the allylic gem-palladium/boryl species take part in the stereoselective cyclopropanation of strained alkenes, 6 carbene dimerization reaction, 7 and three-component coupling reaction with aldehydes and triorganoboranes (Scheme 1). 8 During the course of our study of three-component coupling reactions, a palladium-catalyzed methodology for diastereoselective synthesis of homoaldol equivalent products was discovered during a control reaction attempt in the absence of a triorganoborane; the palladium-catalyzed reaction of 3-(pinacolatoboryl)allyl acetates 1 and aldehydes 2 gave anti-(Z)-δ-hydroxy vinyl acetates 3 with high levels of diastereoselectivity and alkene stereocontrol.…”
Section: Introductionmentioning
confidence: 99%
“…1179) from allyl acetates that contain metal groups (e.g. 1176) [1144]. In the proposed mechanism, a palladium carbene complex (e.g.…”
Section: B Group 10 Carbene Complexes As Transient Intermediatesmentioning
confidence: 99%